Penerapan Metode Entropy dan MOORA Dalam Pemilihan Investasi Saham LQ45 Berbasis Keputusan - Merliana Putri Hasibuan; Samsudin; Muhammad Dedi Irawan (STMIK Budi Darma, 2023)
Stock investment in companies it is a task of the numerous speculative possibilities that is really well-liked in different areas. Due to the large number of enthusiasts, many potential investors invest performing a detailed examination company, resulting in future losses. So to choose the right company to invest in stocks, various considerations are needed. One of the considerations used in investing in stocks is the company's fundamental analysis, where prospective investors can analyze the condition of a company through financial reports to see whether the company is feasible or not to invest. The stock category that is of concern to investors is the LQ45 stock index. When selecting stocks with a promising future, the LQ45 stock index serves as a reference point. To facilitate potential investors in evaluating or analyzing the current condition of the company, an aid to decision-making is required. This decision support system employs entropy and MOORA, or Multi Objective Optimization on the Basis of Ratio Analysis. The weight of each criterion is established by applying the Entropy technique, and the MOORA method is used to rank the alternatives. In this decision support system, the combination of the Entropy and MOORA approaches takes the shape of a weighted ranking of the 7 alternative choices from highest to lowest scores based on the 7 criteria. In accordance with the study's conclusions, this system can deliver best LQ45 stock recommendations that are worthy of investment for potential investors. And the results of the accuracy of manual calculations with system calculations reach 100%.